2001
DOI: 10.1016/s0304-4203(00)00109-2
|View full text |Cite
|
Sign up to set email alerts
|

Total organic carbon distribution and budget through the Strait of Gibraltar in April 1998

Abstract: In order to investigate total organic carbon TOC exchange through the Strait of Gibraltar, samples were taken along two Ž. Ž. sections from the western Gulf of Cadiz and eastern Western Alboran Sea entrances of the Strait and at the middle of thé Strait in April 1998. TOC was measured by using a high-temperature catalytic oxidation method. The results referenced here are based on a three-layer model of water mass exchange through the Strait, which includes the Atlantic inflow, Mediterranean outflow and an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 50 publications
5
47
0
1
Order By: Relevance
“…Finally, regarding the LDW, our archetypal concentration, 44.1 6 0.5 mmol kg 21 , was 3.6 mmol kg 21 above the DOC of Antarctic bottom water (AABW) reported by Carlson et al (2010), but note that whereas the archetypal depth of our LDW was 3700 6 159 10 24 Pa, the average depth of AABW was 5019 10 24 Pa. Regarding the archetypal DOC concentration of MW, 47.3 6 0.7 mmol kg 21 , it was significantly lower than the expected concentration of 48.8-49.3 mmol kg 21 obtained when mixing the Mediterranean overflow water (MOW) of the Strait of Gibraltar (45-46 mmol kg 21 ; Dafner et al 2001) with the SPMW (50.5 6 0.6 mmol kg 21 ; Fig. 4a) in a MOW : SPMW proportion of 0.25-0.34 to form the MW (Rogerson et al 2012).…”
Section: Discussionmentioning
confidence: 64%
“…Finally, regarding the LDW, our archetypal concentration, 44.1 6 0.5 mmol kg 21 , was 3.6 mmol kg 21 above the DOC of Antarctic bottom water (AABW) reported by Carlson et al (2010), but note that whereas the archetypal depth of our LDW was 3700 6 159 10 24 Pa, the average depth of AABW was 5019 10 24 Pa. Regarding the archetypal DOC concentration of MW, 47.3 6 0.7 mmol kg 21 , it was significantly lower than the expected concentration of 48.8-49.3 mmol kg 21 obtained when mixing the Mediterranean overflow water (MOW) of the Strait of Gibraltar (45-46 mmol kg 21 ; Dafner et al 2001) with the SPMW (50.5 6 0.6 mmol kg 21 ; Fig. 4a) in a MOW : SPMW proportion of 0.25-0.34 to form the MW (Rogerson et al 2012).…”
Section: Discussionmentioning
confidence: 64%
“…[7] The study area and the hydrographic conditions found in the Strait of Gibraltar in April 1998 have been already described in greater detail [Dafner et al, 2001]. The Redfield molar ratios based on individual nutrient concentrations ( Figure 2, second line) suggest that the N:Si:P ratios in the Atlantic water at the western entrance of the Strait are lower than the classical Redfield ratio.…”
Section: Resultsmentioning
confidence: 90%
“…Samples were also taken at few meters from the bottom. A detailed description of the depth profiles and bottled sampling are shown in Dafner et al [2001].…”
Section: Methodsmentioning
confidence: 99%
“…Clearly, inputs from the atmosphere and land contribute not only nutrients to support primary production but also reduced, potentially respirable carbon. To complete the picture, we should also consider the net DOC input through Gibraltar, which is in the order of 0.3×10 12 mol C y −1 (Dafner et al, 2001). Inputs from the Black Sea would amount to 10% of those entering through Gibraltar (Sempéré et al, 2002), but a significant part of them are likely processed within the Aegean Sea, thus not affecting the overall picture.…”
Section: Physical and Chemical Frameworkmentioning
confidence: 99%